Modeling cumulative sound exposure over large areas, multiple sources, and long durations - Erbe, Christine (Springer New York LLC, 2012)
Guidelines and regulations for underwater noise exposure tend to focus on single events. For example, the noise field from a single strike on a pile during pile driving or from a single discharge of a seismic air gun array is mapped through either modeling or field measurements, and mitigation zones are defined based on ranges to thresholds commonly expressed as sound pressure level (SPL) or sound exposure level (SEL). In many situations, however, animals will experience ongoing or repeated exposure. The effects of cumulative exposure, the way in which effects from single exposures accumulate, and the potential for recovery between repeated exposures are poorly understood. Another (computational) challenge is to predict, through modeling, cumulative levels received by animals from multiple sources, from moving sources, and from multiple exposures over long durations and large areas. The following sections outline the steps to solve the computational problem for selected example cases.